Penerapan Metode Design Thinking Dalam Membangun Aplikasi Sumber Daya Manusia (Human Resources) - Shie, Carolline; Riani, Evi (Journal of Digital Ecosystem for Natural Sustainability, 2023)
A company certainly has human resources that must be managed. The process of managing human resources has been computerized, but most of it is still manual and because of that the Human Resources Department (HRD) find it difficult to manage. The problem that is often encountered in managing employee data is the difficulty of recording, storing, and managing employee data due to the large number of employees. The purpose of this research is to build a Human Resources (HR) applications that makes it easier for HR to record employee data. The design of this applications uses the Design Thinking method which consists of empathize, define, ideate, prototype, and test stages. The aim of the design is for researchers to have a deep interest in developing understanding from users. This helps researchers to observe and develop empathy with the target users. The result of this research is the applications of Human Resources which can make it easier to overcome difficulties in recording, storing, and managing employee data.